SYSTEM PROBLEM`S OF BANKRUPT IN RUSSIA - S. Е. Кovan (Real Economics Publishing House, 2014)
Mechanism of bankrupt procedure Implementation was analyzed, which were identified current system problems, happened by imperfect of law, presented proposals to developing it. The special attention on  protection of the rights of entrepreneurs in case of bankrupt, which  is now use to be macroeconomic factor, it have big influence on economic of country and entrepreneurs business. It seems reasonable to change way of initiation case of bankrupt by conceptual, from debtor`s side, correcting of methodology and criteria of identification sings in fiction bankrupt, need improve  process of bankrupt in natural monopolies, mostly housing, need to keep working on project of law about trans-boundary  insolvency,  raising the rights and responsibilities to arbitration managers.